OPINION of the International Law Advisory Board, the Ministry of Foreign Aﬀairs of the Russian Federation. PROBLEMS OF LEGALITY OF THE INTERNATIONAL CRIMINAL COURT (translation by graduate students V.V. Pchelintseva and A.M. Korzhenyak) - artikle Editorial (Московский журнал международного права, 2024)
.